Inside Back Cover: Kinetically Controlled Sequential Growth of Surface‐Grafted Chiral Supramolecular Copolymers (Angew. Chem. Int. Ed. 25/2016). Issue 25 (20th May 2016) - Frisch, Hendrik; Fritz, Eva‐Corinna; Stricker, Friedrich; Schmüser, Lars; Spitzer, Daniel; Weidner, Tobias; Ravoo, Bart Jan; Besenius, Pol
Abstract : A modular strategy for the synthesis of surface‐confined supramolecular copolymers is reported by P. Besenius, B. J. Ravoo, and co‐workers in their Communication onpage 7242 ff. The sequential addition of aqueous solutions containing the anionic or cationic comonomer enables the stepwise growth of alternating copolymers from gold surfaces. Charge regulation passivates the growing chain end and yields kinetically trapped chiral copolymers with a tunable height of 5–19 nm.